Structural Transformation and Spillovers from Industrial Areas - David Blakeslee; Ritam Chaurey; Ram Fishman; Samreen Malik (Institute of Labor Economics (IZA), 2018)
Like many developing countries, India features a variety of land-use restrictions that make it difficult to establish industrial firms on agricultural lands. Such policies have received some of the blame for the slow pace of industrialization, and there is widespread agreement on the need for reform. Traditional agrarian economies, however, have many features that may serve as barriers to industrialization, making it unclear that land-use reform would be sufficient for promoting manufacturing growth in rural areas. To better understand the role played by such regulations, we study the effects of the Industrial Areas (IAs) program in India, which facilitated the establishment of industrial firms in areas that had previously been restricted to agriculture. We find that IAs caused a large increase in the number of firms and employment, and that there were substantial spillovers to neighboring villages. Furthermore, IAs trigger a classic "structural transformation" of the economy, with a shift of workers from agricultural to non-agricultural employment, and the creation of numerous small manufacturing and agricultural firms.
Keywords: O12; O25; R2; 330; industrial areas; spillovers; labor market